Captain Underpants and the Preposterous Plight of the Purple Potty People - Pilkey, Dav 1966; Garibaldi, Jose; Barba, Corey (New York Scholastic Inc., 2019)
Harold and George's time-traveling Purple Potty lands them in an alternate universe where everything seems delightful, but evil lurks just beneath the surface, and leads to a battle between Captain Underpants and his own evil twin.
The often told untold story of Captain Underpants -- George and Harold -- Those wacky grown-ups -- The school of hard knocks -- Purple Pottyville -- Strangers in paradise lost -- The world according to George -- Gettin' outta town -- The preposterous plight of Captain Blunderpants -- Not without my hamster (...and my pterodactyl) -- Hypno-horror -- Crackers to the rescue -- Ka-blamski! -- Purple potty people unite! -- The chapter where some stuff happens -- Super supper -- The adventures of Boxer Boy and Great-Granny Girdle -- Meanwhile, back at the tree house... -- Crash! -- Whenhamstersattack.com -- The incredibly graphic violence chapter, part 1 (in Flip-O-Rama) -- The anti-climactic chapter -- Ka-boom! -- Two minutes later... -- Nobody messes with our grandbabies! -- The incredibly graphic violence chapter, part 2 (in Flip-O-Rama) -- Shrinky-dorks -- The incredibly graphic violence chapter, part 3 (in Flip-O-Rama) -- Wrapping things up -- To make a long story short -- To make a longer story even shorter -- The chapter where nothing bad happens -- The thing that could be worse than going to jail for the rest of our lives.
"Full color."
Accelerated Reader AR
Reading Counts
Lexile
114135
Keywords: Captain Underpants -- (Fictitious character) -- Juvenile fiction; Schools -- Juvenile fiction; Heroes -- Juvenile fiction; School principals -- Juvenile fiction; Juvenile Fiction / Readers / Chapter Books; Juvenile Fiction / Humorous Stories; Juvenile Fiction / Action & Adventure / General; School stories; Heroes and heroines -- Fiction; Fiction; Humorous fiction; Juvenile works